Alright, buckle up buttercup. For the first one, you multiply 2 by 4 to get 8, then add 5 to get 13, and finally subtract 8 multiplied by 2 to get -3. For the second one, you multiply 2 by 4 to get 8, then add 7 and 1 to get 16, and finally divide that by 4 multiplied by 2 to get 2. You're welcome.
The reciprocal of any number or expression is 1 divided by that number or expression. So, the reciprocal of 4x2 - 5x - 3 is simply 1 / (4x2 - 5x - 3).The reciprocal of any number or expression is 1 divided by that number or expression. So, the reciprocal of 4x2 - 5x - 3 is simply 1 / (4x2 - 5x - 3).The reciprocal of any number or expression is 1 divided by that number or expression. So, the reciprocal of 4x2 - 5x - 3 is simply 1 / (4x2 - 5x - 3).The reciprocal of any number or expression is 1 divided by that number or expression. So, the reciprocal of 4x2 - 5x - 3 is simply 1 / (4x2 - 5x - 3).
4x2 = -12x, divide both sides by 4x: x = -3
With a calculator.
x3 + 4x2 + 6x + 24 = (x2 + 6)(x + 4)
First you need to solve for y. So write 4x2+y=16 so y=16-4x2 Now write f(x)=16-4x2
4x2+50x = 0 4x(x+12.5) = 0 x = 0 or x = -12.5
-5
So the problem is: Solve: 4x2 - x = 3
Given 3x3 + 4x2 +x + 7 is divided by x2 + 1, find the results:
4x2 - 2x - 3 = 0 (2x + 1)(2x - 3) = 0 x = -(1/2) or (3/2)
4x2 - 9 = (2x + 3)(2x - 3)
(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)